A Study of Educational Administration Problems in Primary Schools: Exploring Challenges in Primary School Administration (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Primary education is the foundation of education and, compared with primary schools, primary schools are very close to the community. Community participation in the administration of primary school is therefore more important. The head teacher of primary school takes care of numerous other responsibilities. We should concentrate on the main problems of head teachers and make some good suggestions. Theoretics, principles and practices, pedagogy not applications in the education system need to be established in research not evaluation. Only head teachers can change the school environment in a sustainable way. 'Good Capitan may sail the ship in the right direction,' certainly, but the captain will certainly not move in the right direction if he has a bed instrument and lazy ineffective co-working people. So the factors that influence rural primary education must be found and the work of the heads of schools must be affected. The factors that influence the education system and lead teachers to create problems include social changes, the time-consuming, political environment, economic conditions, technological developments, changes in the nature of work etc.